Biomass and biofuel crop effects on biodiversity and ecosystem services in the North Central US. (July 2018) - Landis, Douglas A.; Gratton, Claudio; Jackson, Randall D.; Gross, Katherine L.; Duncan, David S.; Liang, Chao; Meehan, Timothy D.; Robertson, Bruce A.; Schmidt, Thomas M.; Stahlheber, Karen A.; Tiedje, James M.; Werling, Benjamin P.
Abstract: Biomass cropping systems have the potential to alter the ecosystem services provided by agricultural landscapes. Depending on crop type and management, strategic incorporation of biomass cropping systems into existing agricultural landscapes could enhance a range of ecosystem services while mitigating some disservices. Here, we review the approaches and findings of eight years of research into the potential effects of a range of biomass cropping systems on ecosystem services in the North Central US. Our research was framed by an initial assessment of the abundance and distribution of multiple taxa (i.e., biodiversity) within candidate biomass cropping systems. The processes underpinning important ecosystem services in each system were then measured or modeled, related to biodiversity metrics, and used to explore the influence of management scenarios on biodiversity and ecosystem processes. We also used these data and models to develop a decision support system that allows stakeholders to consider tradeoffs and synergies under alternative landscape composition, configuration, and agronomic management. Perennial grass cropping systems provided the greatest potential to promote multiple ecosystem services. More diverse perennial grasslands that include forbs have the potential to increase pest suppression and pollination, decrease greenhouse gas emissions, and enhance grassland bird communities, but likely at the expense of biomass yield. Providing stakeholders and policymakers with information about the expected mix of ecosystem services supported by different biomass feedstock cropping systems in advance of their adoption offers the potential for informed choices to guide the implementation and management of future biomass-producing landscapes. Highlights: Biodiversity and ecosystem services of biomass crops were studied at plot to landscape levels. Metrics of biodiversity included taxonomic richness of plants, insects, soil microbes and birds. Biodiversity and ecosystem processes generally increased with increasing perenniality and within-crop diversity. Evaluating tradeoffs among ecosystem services can inform biomass crop selection and placement in agricultural landscapes.